Manufactory : promoting 3D spatial skills with productive failure and educational games - Tian, Nana (2021)
This research study investigated an innovative teaching and learning framework that incorporated the proven concept of Productive Failure (PF) and educational games. The aim is to design a new approach that effectively enhances students' learning experience and improves their understanding capacities in the threshold concepts of product manufacturing and assembly. As a measure to promote active learning, an educational game is introduced in the problem-solving phase of PF. To be precise, a 3D puzzle game named 'Manufactory' was designed and implemented to assist students in improving their 3D spatial abilities. In order to evaluate the presented framework, an interactive experiment was conducted where students were allocated to Productive Failure (PF) group or Direct Learning (DL) group. In the former group, students are first required to solve the problems in the puzzle game independently before instructions are given in the second stage. Meanwhile, the conventional teaching approach is conducted in the latter group. Experimental results reflect that students in the PF group have achieved a distinctive improvement, raising their average score by 40% and has outperformed students in the DL group with 22% greater progression during the post-test. This demonstrates that our 3D educational game design provided an engaging environment for the problem-solving phase, which serves as the primary motivation for effective absorption of the concepts in the delayed instruction phase. Suggestions for improving the design of PF and educational game are discussed.